The Dialectic of Ishlah Principle: Contextualizing Reconciliation on the Dominant Factors of Divorce - Rahim, Dinaryati (SIGn Jurnal Hukum, 2025)
The uniform application of mediation in divorce cases in Indonesia has proven unevenly effective, particularly when confronted with conflicts that undermine the essence of marriage, the sacred covenant (mitsaqan ghalizhan), such as domestic violence. Addressing this problem, this study critically analyses the dialectic between the imperative of the Reconciliation principle (ishlah) and the heterogeneity of factors that cause divorce. Employing a normative-qualitative legal research method and an Islamic legal philosophy approach, this study operationalizes the framework of the higher objectives of shari’ah (maqasid al-shari’ah) as its primary analytical tool. The findings reveal an apparent dichotomy. Mediation holds potential for success in functional-relational conflicts, such as economic factors and persistent disputes (syiqaq). However, it proves ineffective and philosophically inappropriate in cases of fundamental violations like domestic violence and infidelity, as it contradicts the objective of the preservation of life (hifz al-nafs). This research concludes that the paradigm of success in mediation must be reconceptualized. It must shift from merely achieving a formal marital reunion (rujuk) to realizing an amicable divorce (tasrihun bi ihsan), wherein a peaceful agreement on post-divorce rights becomes the primary metric. Therefore, the development of conflict typology-based mediation guidelines is recommended to align legal practice with substantive justice.